Book history's recent methodological trend: national and intemational outlines - Jyrki Hakapää (Knygotyra)
About twenty years ago, Robert Darnton famously wrote about how books know no frontiers. Nevertheless, as the discipline of book history has established itself around the world, many comprehensive works on the research field have determined themselves according to the nation-state borders. As national needs have been recently fulfilled in many countries, international and cosmopolitan themes and studies have received a new kind of support. In a world marked by globalization, such a change in attitude seems reasonable.